2022
DOI: 10.3390/coatings12081176
|View full text |Cite
|
Sign up to set email alerts
|

Strength of Fiber Posts with Experimental TiO2 and ZrO2 Particle Bonding—An SEM, EDX, Rheometric and Push-Out Strength Study

Abstract: The present study aimed to prepare experimental adhesives (EAs): 5 wt.% titanium dioxide (TiO2) adhesive; and 5 wt.% zirconium oxide (ZrO2) adhesive; and analyze their impact on bond integrity of fiber posts to root dentin, and viscosity. The EA was composed of: bisphenol A glycol dimethacrylate (BisGMA); triethylene glycol dimethacrylate (TEGDMA); 2-hydroxyethyl methacrylate (HEMA); and ethyl 4-dimethylamino benzoate and camphorquinone. TiO2 and ZrO2 particles were individually incorporated into the EA at 5 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Several earlier studies have presented that the presence of inorganic filler NPs augments dentin adhesive’s push-out, micro-tensile, and shear bond strength. 4,39 Previously, Khan et al revealed that including GNPs inside the adhesive improves its bond strength. 40 Bin-Shuwaish et al reported identical findings and conveyed that adding GNPs to the adhesive’s composition could amplify its bond strength.…”
Section: Discussionmentioning
confidence: 99%
“…Several earlier studies have presented that the presence of inorganic filler NPs augments dentin adhesive’s push-out, micro-tensile, and shear bond strength. 4,39 Previously, Khan et al revealed that including GNPs inside the adhesive improves its bond strength. 40 Bin-Shuwaish et al reported identical findings and conveyed that adding GNPs to the adhesive’s composition could amplify its bond strength.…”
Section: Discussionmentioning
confidence: 99%